ANTIMICROBIAL EFFICACY AND PHYTOCHEMICAL ANALYSIS OF INDIGOFERA TRITA LINN. - Kumar, Raju Senthil; Moorthy, Kannaiyan; Vinodhini, Raja; Punitha, Thambidurai (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
An in vitro antimicrobial activity and phytochemical analysis of various extracts of Indigofera trita L. viz. petroleum ether, chloroform, acetone, ethanol and aqueous extracts were carried out. A total of 21 microorganisms (19 bacteria and 2 fungal strains) were used for antimicrobial activity by disc diffusion method and a standard procedure was used to identify the phytochemical constituents. Petroleum ether extract showed moderate inhibitory activity against Staphylococcus aureus (14.40 mm), S. epidermidis (14.20 mm), Salmonella paratyphi A (12.80 mm), Streptococcus mutans (12.20 mm), Escherichia coli, Proteus vulgaris, S. typhi and Burkholderia cepacia (12.00 mm). The chloroform extract also showed antimicrobial activity against S. epidermidis (14.20 mm), S. typhimurium (12.60 mm), S. paratyphi A, S. brunei and Yersinia enterocolitica (12.00 mm). The acetone extract of I. trita showed considerable inhibitory activity against S. epidermidis (18.20 mm), S. typhimurium (14.60 mm), S. infantis (13.80 mm), S. aureus (13.40 mm), Y. enterocolitica (13.00 mm) and Enterobacter aerogenes (12.00 mm) were documented. Ethanol extract showed significant antimicrobial activity against S. epidermidis (18.60 mm), S. paratyphi A (14.60 mm), Y. enterocolitica (13.40 mm), S. typhi (12.40 mm), S. aureus, E. aerogenes, S. typhimurium and S. infantis (12.00 mm). Aqueous extract of I. trita considerably inhibited S. epidermidis (13.80 mm), S. paratyphi A and Y. enterocolitica (12.20 mm), E. aerogenes and Haemophilus parahaemolyticus (12.00 mm). All the five extracts showed a minimal antifungal activity when compared to antibacterial activity. The result revealed that the antimicrobial properties of I. trita might be associated with the presence of phenolic compounds, flavonoids, tannins, glycosides, saponins, phytosterols and alkaloids.